ORIENTASI KARIR PADA PESERTA DIDIK DI SMA NEGERI 1 SUNGAI RAYA - Saputri, Yessiana Yolanda; Purwanti, Purwanti; Yusuf, Abas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe students? career orientation of SMA is a process to election the students? further education and the occupation with the clear objective, self-understanding, considerations of opportunities, the exploration of the information, and planning for the future. After the students pass the graduation stage in Senior High School then, they should continue to college level education. This process effect by several things such as the potential of students? academic, supporting from their parents, the readiness of their mental as well as their knowledge and understanding of career orientation. Based on Sharf, aspect of career orientation has two components; there are Career Development Attitude and Career Development Knowledge and Skill. The purpose in this research is to describe the students? career orientation in SMA Negeri 1 Sungai Raya. The method that used in this research is descriptive method. Based on this research the result showed that the whole career orientation was 76% with the ?High? category. Then, career development attitude was 76% with the ?High? category, besides career development knowledge and skill was 76% with the ?High? category. It was showed that the career orientation effected by two components; Career Development Attitude and Career Development Knowledge and Skill.Keywords: Career Orientation, Education, College